Pembelajaran Fiqh Di SD Kartika 3 - Siti Fauziah, Ismi; Shevila Wigar, Lingga (Ar-Rusyd: Jurnal Pendidikan Agama Islam, 2025)
This study aims to determine the evaluation of the learning process of Islamic Religious Education (PAI) in SD Kartika 3 and to determine the learning process of Islamic Religious Education (PAI) especially the fiqh chapter. This study is a qualitative research field. Data collection methods in the form of documentation, interviews, observations. Data analysis techniques using qualitative analysis. The results showed that first, the learning process of Islamic Religious Education (PAI) which took place at SD Kartika 3 was in accordance with the planned program. a) in the use of media/methods teachers have used media / approaches in the learning process with variations. But the lecture method is still predominantly used. B) the available Teacher Resources are sufficient to meet the qualifications and standards of the learning process of Islamic Religious Education. C) conducive class management although still found some students are less enthusiastic in learning d) facilities and infrastructure are quite complete and support the process of learning activities.